2021
DOI: 10.1371/journal.pone.0245329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 0.05% cyclosporine A on the lipid layer and meibomian glands after cataract surgery: A randomized, double-masked study

Abstract: Purpose To quantitatively evaluate the effects of 0.05% cyclosporine A (CsA) on lipid layer thickness (LLT) and meibomian glands after cataract surgery using the LipiView® ocular surface interferometer. Methods This study was a prospective randomized double-masked clinical trial conducted by Pusan National University Yangsan Hospital between April 04, 2019, and November 31, 2019. Sixty-two participants were recruited, and 12 of them were not enrolled because they had undergone previous treatments for ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In line with our results, Kang et al . 31 found a significant improvement in the TBUT score in subjects who received treatment with cyclosporine 0.05% compared with the group treated with 0.5% carboxymethylcellulose. Furthermore, in patients treated with topical lubricants and cyclosporine 0.05%, Ganesh et al .…”
Section: Discussionmentioning
confidence: 80%
“…In line with our results, Kang et al . 31 found a significant improvement in the TBUT score in subjects who received treatment with cyclosporine 0.05% compared with the group treated with 0.5% carboxymethylcellulose. Furthermore, in patients treated with topical lubricants and cyclosporine 0.05%, Ganesh et al .…”
Section: Discussionmentioning
confidence: 80%
“…Our results show that dry eye symptoms and ocular surface dysfunction signs are quite common before the cataract surgery, and they only worsen after phacoemulsification. There are a few studies that evaluated medications for dry eye symptoms and signs occurring after the phacoemulsification: trehalose/sodium hyaluronate [ 46 ], trehalose/hyaluronic acid vs. hyaluronic acid [ 47 ], 3% diquafosol [ 48 ], and 0.05% cyclosporine A [ 49 ] which all had positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of cyclosporine on LLT has been limitedly investigated. In a previous study, significant improvement in LLT after 3mo of using conventional cyclosporine was reported [39] . This study also showed significant changes occurred after 8wk of treatment with conventional cyclosporine, In contrast, the Nano-cyclosporine group showed statistically significant change in LLT after 4wk.…”
Section: Commentioning
confidence: 91%